Revision of the Litoria watjulumensis (Anura: Pelodryadidae) group from the Australian monsoonal tropics, including the resurrection of L. spaldingi - Donnellan, Stephen C.; Catalano, Sarah R.; Pederson, Stephen; Mitchell, Kieren J.; Suhendran, Aidan; Price, Luke C.; Doughty, Paul; Richards, Stephen J. (Zootaxa, 2021)
We show that the Wotjulum frog, Litoria watjulumensis (Copland, 1957), comprises two deeply divergent mitochondrial DNA lineages that are also reciprocally monophyletic for a nuclear gene locus and have discrete distributions. The taxa are differentiated in multivariate analysis of shape but show no appreciable differences in colour and pattern. The two taxa differ substantially in the degree of female biased sexual size dimorphism, with the western taxon showing considerably more pronounced dimorphism. We subsequently resurrect Litoria (Hyla) spaldingi (Hosmer, 1964) for populations from east of the Daly River system in the Northern Territory through to western Queensland and restrict L. watjulumensis to populations from the Kimberley region of north-western Australia and the Victoria River system of the western Northern Territory. The complex advertisement call of L. spaldingi is described for the first time.